UTILIZATION OF PINEAPPLE WASTE AS A RAW MATERIAL FOR BIOETHANOL - Hana Eldiana Yuliani; Selfi Aprillia Ningrum, Ainun Nafiatus Ulfah, Haliza Nurul Amin, Gita Maylita Sari, Endah Rita Sulis (ADISAM Publisher, 2023)
Indonesia has large natural vegetable resources to be able to provide a promising and environmentally friendly alternative fuel to replace petroleum, namely bioethanol. Bioethanol is a biochemical liquid from the process of fermenting sugar from carbohydrate sources using the help of microorganisms. Bioethanol is produced from biomass containing sugar, starch and cellulose. One of the raw materials for bioethanol which is environmental waste is pineapple skin and pineapple hump. In this literature review, 15 articles were collected relating to the utilization of fruit waste as a raw material for bioethanol production and its effectiveness. The results from the literature review show that pineapple waste has suitable characteristics to be used as raw material for making bioethanol which is useful for environmentally friendly alternative fuels.